ADAPTATION AND VALIDATION OF FIVE FACTOR MINDFULNESS QUESTIONNAIRE - Yaryna Kaplunenko; Valerie Kuchyna (International Journal of Innovative Technologies in Social Science, 2022)
The mindfulness approach, which in recent years has been actively integrated into daily life and clinical psychological practice, has shown its high effectiveness in reducing stress, overcoming symptoms of anxiety, anxiety, depression, burnout, and other psychological difficulties. To date, many techniques have been developed to measure this ability, which is important for assessing the initial human condition and the effectiveness of therapeutic effects. The article reflects the results of adaptation and validation of the Ukrainian version of the English-language questionnaire R. Bayer and co-authors - "Five-Facet Mindfulness Questionnaire (FFMQ). The analysis of psychometric properties of the Ukrainian version of the questionnaire (internal consistency, correlation of scales, constructive validity) is presented, the factor structure and interrelations of various aspects of awareness and indicators of mental health are analyzed. The adapted technique showed very good results during the validation - the original five-factor structure was reproduced with the same factors as the original, the scales of which showed high reliability. The adaptation of the method was carried out in accordance with all standard requirements for the adaptation of foreign language psychodiagnostic tools. The study involved 253 people.